Targeting the epidermal growth factor receptor in non-small cell lung cancer cells: the effect of combining RNA interference with tyrosine kinase inhibitors or cetuximab - Chen Gang; Kronenberger Peter; Teugels Erik; Umelo Ijeoma; De Grève Jacques (BMC Medicine, 2012)
Abstract Background The epidermal growth factor receptor (EGFR) is a validated therapeutic target in non-small cell lung cancer (NSCLC). However, current single agent receptor targeting does not achieve a maximal therapeutic effect, and some mutations confer resistance to current available agents. In the current study we have examined, in different NSCLC cell lines, the combined effect of RNA interference targeting the EGFR mRNA, and inactivation of EGFR signaling using different receptor tyrosine kinase inhibitors (TKIs) or a monoclonal antibody cetuximab. Methods NSCLC cells (cell lines HCC827, H292, H358, H1650, and H1975) were transfected with EGFR siRNA and/or treated with the TKIs gefitinib, erlotinib, and afatinib, and/or with the monoclonal antibody cetuximab. The reduction of EGFR mRNA expression was measured by real-time quantitative RT-PCR. The down-regulation of EGFR protein expression was measured by western blot, and the proliferation, viability, caspase3/7 activity, and apoptotic morphology were monitored by spectrophotometry, fluorimetry, and fluorescence microscopy. The combined effect of EGFR siRNA and different drugs was evaluated using a combination index. Results EGFR-specific siRNA strongly inhibited EGFR protein expression almost equally in all cell lines and inhibited cell growth and induced cell apoptosis in all NSCLC cell lines studied, albeit with a different magnitude. The effects on growth obtained with siRNA was strikingly different from the effects obtained with TKIs. The effects of siRNA probably correlate with the overall oncogenic significance of the receptor, which is only partly inhibited by the TKIs. The cells which showed weak response to TKIs, such as the H1975 cell line containing the T790M resistance mutation, were found to be responsive to siRNA knockdown of EGFR, as were cell lines with downstream TKI resistance mutations. The cell line HCC827, harboring an exon 19 deletion mutation, was more than 10-fold more sensitive to TKI proliferation inhibition and apoptosis induction than any of the other cell lines. Cetuximab alone had no relevant in vitro activity at concentrations obtainable in the clinic. The addition of EGFR siRNA to either TKIs or cetuximab additively enhanced growth inhibition and induction of apoptosis in all five cell lines, independent of the EGFR mutation status (wild-type or sensitizing mutation or resistant mutation). The strongest biological effect was observed when afatinib was combined with an EGFR-specific siRNA. Conclusions EGFR knockdown by siRNA further decreases the cell growth of lung cancer cells that are treated with TKIs or cetuximab alone, confirming that single agent drug targeting does not achieve a maximal biological effect. The siRNA inhibits EGFR oncogenic activity that bypasses downstream "resistance" mutations such as KRAS and PTEN. The combined treatment of siRNA and EGFR inhibitory agents is additive. The combination of a potent, irreversible kinase inhibitor such as afatinib, with EGFR-specific siRNAs should be further investigated as a new strategy in the treatment of lung cancer and other EGFR dependent cancers, including those with downstream resistance mutations.